Fast dissolving moxifloxacin hydrochloride antibiotic drug from electrospun Eudragit L-100 nonwoven nanofibrous mats - Giram, Prabhanjan S.; Shitole, Ajinkya; Nande, Smita S.; Sharma, Neeti; Garnaik, Baijayantimala (Materials Science & Engineering C-Materials For Biological Applications, 2018)
Antimicrobial electrospun nonwoven Eudragit L-100 nanofibrous mats containing Moxifloxacin hydrochloride (MOX-HCL) were fabricated for fast dissolving drug delivery systems (DDSs) associated with wound infection. The morphological characterization of nanofibers using ESEM revealed that the average diameter of non-woven nanofibrous mats ranges 200-600 nm. The nanofiber showed cylindrical shape with crack on the surface. Differential scanning calorimetric (DSC) and Wide Angle X-ray diffraction (WAXRD) demonstrate that the drug exists in an amorphous state in the nanofibers. Nanofibrous mats were also tested for mechanical strength, contact angle, swelling assay, haemolysis and disintegration test. In vitro disintegration tests demonstrated that the dissolution of Eudragit L-100 fiber mats was within 25 s which was higher compared to the pure drug. The Eudragit nanofibers showed pH-dependent drug release profiles, with slow release at pH 1.2 and burst release (around 30 s) at pH 6.8. The in-vitro quantitative and qualitative antimicrobial assay showed that the developed Eudragit L-100 nanofibrous mats with MOX-HCL concentration of 1%, 5% and 15 wt% exhibited antibacterial activities against both gram positive (Staphylococcus aureus) and gram negative (Escherichia coli) bacteria. The invitro cytotoxicity assay using mouse fibroblast NIH/3T3 cells demonstrated significant biocompatibility of nanofiber mats. As per the results of biological evaluation, Eudragit L-100 nanofibrous mats with 1wt% MOX-HCL could be a suitable substrate for biomedical applications. Eudragit L-100 nanofibrous mats containing Moxifloxacin hydrochloride (MOX-HCL) showed immediate DDSs for localized drug release in the wound infection at slightly acidic or alkaline conditions where faster drug release rate is required for wound healing.

Clopidogrel eluting electrospun polyurethane/polyethylene glycol thromboresistant, hemocompatible nanofibrous scaffolds - Shitole, Ajinkya A.; Giram, Prabhanjan S.; Raut, Piyush W.; Rade, Priyanka P.; Khandwekar, Anand P.; Sharma, Neeti; Garnaik, Baijayantimala (Journal of Biomaterials Applications, 2019)
Biomaterials used as blood-contacting material must be hemocompatible and exhibit lower thrombotic potential while maintaining hemostasis and angiogenesis. With the aim of developing thromboresistant, hemocompatible nanofibrous scaffolds, polyurethane/polyethylene glycol scaffolds incorporated with 1, 5, and 10 wt% Clopidogrel were fabricated and evaluated for their physiochemical properties, biocompatibility, hemocompatibility, and antithrombotic potential. The results of physicochemical characterization revealed the fabrication of nanometer-sized scaffolds with smooth surfaces. The incorporation of both polyethylene glycol and Clopidogrel to polyurethane enhanced the hydrophilicity and water uptake potential of polyurethane/polyethylene glycol/Clopidogrel scaffolds. The dynamic mechanical analysis revealed the enhancement in mechanical strength of the polyurethane/polyethylene glycol scaffolds on incorporation of Clopidogrel. The polyurethane/polyethylene glycol/Clopidogrel scaffolds showed a tri-phasic drug release pattern. The results of hemocompatibility assessment demonstrated the excellent blood compatibility of the polyurethane/polyethylene glycol/Clopidogrel scaffolds, with the developed scaffolds exhibiting lower hemolysis, increased albumin and plasma protein adsorption while reduction in fibrinogen adsorption. Further, the platelet adhesion was highly suppressed and significant increase in coagulation period was observed for Clopidogrel incorporated scaffolds. The results of cell adhesion and cell viability substantiate the biocompatibility of the developed nanofibrous scaffolds with the HUVEC cell viability on polyurethane/polyethylene glycol, polyurethane/polyethylene glycol/Clopidogrel-1, 5, and 10% at day 7 found to be 12.35, 13.36, 14.85, and 4.18% higher as compared to polyurethane scaffolds, and the NIH/3T3 cell viability found to be 35.27, 70.82, 36.60, and 7.95% higher as compared to polyurethane scaffolds, respectively. Altogether the results of the study advocate the incorporation of Clopidogrel to the polyurethane/polyethylene glycol blend in order to fabricate scaffolds with appropriate antithrombotic property, hemocompatibility, and cell proliferation capacity and thus, might be successfully used as antithrombotic material for biomedical application.
Keywords: adhesion; cardiovascular; coagulation; electrospinning; Hemocompatible; platelet

Electrospun polycaprolactone/hydroxyapatite/ZnO nanofibers as potential biomaterials for bone tissue regeneration - Shitole, Ajinkya A.; Raut, Piyush W.; Sharma, Neeti; Giram, Prabhanjan; Khandwekar, Anand P.; Garnaik, Baijayantimala (Journal of Materials Science-Materials In Medicine, 2019)
Fabricating a bioartificial bone graft possessing structural, mechanical and biological properties mimicking the real bone matrix is a major challenge in bone tissue engineering. Moreover, the developed materials are prone to microbial invasion leading to biomaterial centered infections which might limit their clinical translation. In the present study, biomimetic nanofibrous scaffolds of Poly -caprolactone (PCL)/nano-hydroxyapatite (nHA) were electrospun with 1wt%, 5wt%, 10wt%, 15wt% and 30wt% of zinc oxide (ZnO) nanoparticles in order to understand the optimal concentration range of (ZnO) nanoparticles balancing both biocompatibility and osteoregeneration. The developed nanofibrous scaffolds were successfully characterized using scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDAX), contact angle, fourier transform infrared spectroscopy (FTIR), wide-angle X-Ray diffraction (WAXD), brunaueremmett Teller (BET) surface area and tensile testing. Biocompatibility of the developed scaffolds at in vitro level was evaluated by culturing MG-63 cells and investigating the impact on cell viability, proliferation, protein adsorption, alkaline phosphatase (ALP) activity and biomineralization. The PCL/nHA scaffolds exhibited a 1.2-fold increase in cell viability and proliferation, while incorporation of ZnO nanoparticles to PCL/nHA imparted antimicrobial activity to the scaffolds with a progressive increase in the antimicrobial efficacy with increasing ZnO concentration. The results of cell viability were supported by ALP activity and mineralization assay, wherein, PCL/nHA/ZnO scaffolds showed higher ALP activity and better mineralization capacity as compared to pristine PCL. Although, the PCL/nHA/ZnO scaffolds with 10, 15 and 30wt% of ZnO particles exhibited superior antimicrobial efficacy against both gram-negative (E. coli) and gram-positive (S. aureus) bacteria, a significant decrease in the cell viability and mechanical properties was observed at higher concentrations of ZnO namely 15 and 30%. Amongst the various ZnO concentrations studied optimal cell viability, antimicrobial effect and mechanical strength were observed at 10wt.% ZnO concentration. Thus, the present study revealed that the biomimetic tri-component PCL/nHA/ZnO scaffolds with ZnO concentration range of10% could be ideal for achieving optimal biocompatibility (cell proliferation, biomineralization, and antimicrobial capacity) and mechanical stability thus making it a promising biomaterial substrate for bone tissue regeneration. [GRAPHICS] .

LHRH-conjugated, PEGylated, poly-lactide-co-glycolide nanocapsules for targeted delivery of combinational chemotherapeutic drugs Docetaxel and Quercetin for prostate cancer - Shitole, Ajinkya A.; Sharma, Neeti; Giram, Prabhanjan; Khandwekar, Anand; Baruah, Meghna; Garnaik, Baijayantimala; Koratkar, Santosh (Materials Science & Engineering C-Materials for Biological Applications, 2020)
One of the major challenges in effective cancer chemotherapy is the severe systemic cytotoxicities of anticancer drugs on healthy tissues. The present study reports chemically modified polymeric nanocapsules (NCs) encapsulating combination of chemotherapeutic drugs Docetaxel (DTX) and Quercetin (QU) for its active targeting to prostate cancer (PCa). The active targeting was achieved by conjugating Luteinizing-hormone-releasing hormone (LHRH) ligand to poly-lactide-co-glycolide (PLGA) using polyethylene glycol (PEG) as a spacer. The structure of the conjugates was characterized and confirmed using H-1 NMR and ATR-FTIR. The drug encapsulated NCs showed a homogenous size distribution with their size ranging between 120 and 150 nm, and exhibited a negative zeta potential in the range of - 20 to - 40 mV. The in vitro release studies highlighted the sustained drug release pattern from the respective NCs; while the PEG coating to polymeric NCs provided serum stability to the NCs. The in vitro biological evaluation of the NCs was conducted using PC-3 and LNCaP cell lines. The results of the cellular uptake studies showed a significantly higher untake of the LHRH targeted NCs, while the LHRH-targeted-PEGylated DTX: QU NCs exhibited higher caspase-3 activity. The cell viability assay results showed the enhanced cell inhibition activity of the combinatorial DTX: QU when compared to individual DTX. Further, higher cell cytotoxicity was achieved by LHRH-targeted DTX: QU NCs as compared to their free-form or non-targeted NCs. Finally, the results of in vivo tumor localization and in vivo antitumor activity studies complimented and upheld the in vitro results, demonstrating the beneficial role of PLGA-PEG-LHRH NCs encapsulating combination of DTX and QU in combating prostate cancer (PCa).
Keywords: Active targeting; Anticancer; Controlled release; EPR effect; Hydrophobic; Prostate

Poly (vinylpyrrolidone)-iodine engineered poly (epsilon-caprolactone) nanofibers as potential wound dressing materials - Shitole, Ajinkya A.; Raut, Piyush; Giram, Prabhanjan; Rade, Priyanka; Khandwekar, Anand; Garnaik, Baijayantimala; Sharma, Neeti (Materials Science & Engineering C-Materials for Biological Applications, 2020)
Facilitating the process of wound healing and effective treatment of wounds remains a serious challenge in healthcare. Wound dressing materials play a major role in the protection of wounds and in accelerating the natural healing process. In the present study, novel core/shell (c/s) nanofibrous mats of poly(vinyl pyrrolidone)-iodine (PVPI) and polycaprolactone (PCL) were fabricated using a co-axial electrospinning process followed by their surface modification with poly-L-lysine. The developed nanofibrous mats were extensively characterized for their physicochemical properties using various analytical techniques. The core/shell structure of the PVP-I/PCL nanofibers was confirmed using TEM analysis. The PVP-I release studies showed an initial burst phase followed by a sustained release pattern of PVP-I over a period of 30 days. The developed nanofibers exhibited higher BSA and fibrinogen adsorption as compared to pristine PCL. Cytotoxicity studies using MTT assay demonstrated that the PVP-I/PCL (c/s) nanofibers were cytocompatible at optimized PVP-I concentration (3 wt%). The PCL-poly-L-lysine and PVP-I/PCL-poly-L-lysine nanofibers exhibited higher cell viability (24.2% and 21.4% higher at day 7) when compared to uncoated PCL and PVP-I/PCL nanofibers. The PVP-I/PCL nanofibers showed excellent antimicrobial activity against both Gram-positive (S. aureus) and Gram-negative (E. coli) bacteria. The inflammatory response of Mouse RAW 264.7 macrophage cells towards the nanofibers was studied using RTPCR. It revealed that the pro-inflammatory cytokines (TNF-alpha and IL-1 beta) were significantly upregulated on PCL nanofibers, while their expression was comparatively lower on poly-L-lysine coated PCL or PVP-I/PCL(c/s) nanofibers. Overall, the study highlights the ability of poly-L-lysine coated PVP-I/PCL (c/s) nanofibers as potential wound dressing materials effectively facilitating the early stage wound healing and repair process by virtue of their selective modulation of inflammation, cell adhesion and antimicrobial properties.
Keywords: biodegradable; Controlled release; Core/shell; electrospinning; scaffolds; tissue engineering

Physicochemical and in vitro antibacterial evaluation of metronidazole loaded eudragit S-100 nanofibrous mats for the intestinal drug delivery - Rade, Priyanka P.; Giram, Prabhanjan S.; Shitole, Ajinkya A.; Sharma, Neeti; Garnaik, Baijayantimala (Advanced Fiber Materials, 2021)
Metronidazole (MTZ) loaded Eudragit S-100 (ES-100) nonwoven nanofibrous mats were successfully electrospun and evaluated for intestinal drug delivery. MTZ was varied in the range of 1–15% (w/w) in ES-100 nanofibrous mats, the morphological characterization of nanofibrous mats was carried out using FE-SEM and the average diameter of nanofiber was found in the range 150–600 nm. WAXD and DSC demonstrated the amorphous nature of MTZ in ES-100 nanofibrous mats. Their contact angle analysis confirmed the hydrophobic nature. The mechanical strength of ES-100 nanofibrous mats decreased with increasing MTZ concentration. The drug release profiles showed 74% MTZ release from ES-100d within 2 h at pH 6.8 which is the colonic environment. Antibacterial activities against gram-positive bacteria (Staphylococcus aureus) and gram-negative bacteria (Escherichia coli) showed that the ES-100 nanofibrous mats loaded with MTZ exhibited good activity.